2017
DOI: 10.1158/2159-8290.cd-16-0127
|View full text |Cite
|
Sign up to set email alerts
|

Role of KEAP1/NRF2 and TP53 Mutations in Lung Squamous Cell Carcinoma Development and Radiation Resistance

Abstract: Lung squamous cell carcinomas (LSCC) pathogenesis remains incompletely understood and biomarkers predicting treatment response remain lacking. Here we describe novel murine LSCC models driven by loss of Trp53 and Keap1, both of which are frequently mutated in human LSCCs. Homozygous inactivation of Keap1 or Trp53 promoted airway basal stem cell (ABSC) self-renewal, suggesting that mutations in these genes lead to expansion of mutant stem cell clones. Deletion of Trp53 and Keap1 in ABSCs, but not more different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
227
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(242 citation statements)
references
References 73 publications
9
227
5
1
Order By: Relevance
“…Previous evidence also showed that Nrf2 expression was evaluated in HNSCC, and Nrf2 expression may be a possible HNSCC candidate biomarker 17. Upregulation of Nrf2 leads to Keap1 loss that contributes to lung squamous cell carcinomas (LSCC),30 and Nrf2 activity has also been indicated to confer RT in LSCC 31. Induced by multiple kinds of oxidative agents, HO1 is a stress-responsive enzyme that plays an oncogenic role in cancerous or transformed human cells and elevated HO1 expression was detected in malignant tumors, including gastric cancer and breast cancer 32,33.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence also showed that Nrf2 expression was evaluated in HNSCC, and Nrf2 expression may be a possible HNSCC candidate biomarker 17. Upregulation of Nrf2 leads to Keap1 loss that contributes to lung squamous cell carcinomas (LSCC),30 and Nrf2 activity has also been indicated to confer RT in LSCC 31. Induced by multiple kinds of oxidative agents, HO1 is a stress-responsive enzyme that plays an oncogenic role in cancerous or transformed human cells and elevated HO1 expression was detected in malignant tumors, including gastric cancer and breast cancer 32,33.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, increased NRF2 activity, resulting from KEAP1 mutations 114120 , NRF2 promoter hypermethylation 118,121123 or mutations in NRF2 that disrupt KEAP1 association 124 , is a negative prognostic marker in many cancers. Alterations in the KEAP1–NRF2 pathway have been implicated in the pathogenesis of lung cancer, where co-deletion of Keap1 and Trp53 in airway basal stem cells results in the development of lung tumours (upon transplantation of the cells into nude mice) that resemble human lung squamous cell carcinoma (SCC) 125 .…”
Section: Signal Transduction Regulation By Ubiquitin Ligasesmentioning
confidence: 99%
“…For example, mutations in the KEAP1/NRF2 pathway predicted an increased risk of local relapse in patients with locally advanced NSCLC treated with high-dose radiotherapy with or without chemotherapy. 260 Another candidate indicator is the genome-based model for adjusting radiotherapy dose, a composite metric involving a quantitative assessment of the expression of ten individual genes to determine a radiosensitivity index and an equation accounting for the radiation dose schedule. 261 …”
Section: Radiation Oncologymentioning
confidence: 99%